Gambaran Tingkat Pengetahuan Remaja Tentang Premenstrual Syndrome Pada Siswi MTs Ittihad Samarinda - Amalia, Vidia Rizki; Mufidati, Diana (Akademi Kebidanan Bunga Husada Samarinda, 2023)
This Research aims to anylze the description of adolescent,s knowledge level about premenstrual syndrome in female adolescents of Junior High School of MTS Ittihad Samarinda in 2023. This study use applied descriptive research. The data collection technique used total sampling. Reasearch results show that are most of the female students in Junior High School of MTS Ittihad Samarinda had knowledge in moderate level. It is expected that female students can increase their knowledge about premenstrual syndrome in order to deal with it properly and correctly.